Supervisory development course of the National Center for Mental Health an evaluation - Cruz, Angelina Vega
The National Center for Mental Health, having been designated, as a special, teaching, training and research center and hospital, had been conducting various training programs. One of these program was the Supervisory Development Course, which was offered to supervisors in all levels. However, a part of the training program which seemingly had been neglected, was the aspect of evaluation. If ever evaluation was conducted, it was limited to the feelings, opinions or reactions of the trainees towards the training course or perhaps merely on the transfer of knowledge to the participants. No attempt had been done to evaluate the effectiveness of the training program in on-job performance of the participants. Hence, this study was conducted. The study made an analysis of the effectiveness of the Supervisory Development Course, offered at the National Center for Mental Health, from 1980-1984. Analysis of the course syllabi of the 4 Supervisory Course from 1980-1984, revealed similarities in terms of content, objectives and strategies used by the Training Staff. Emphasis was on the Management Functions and Roles of the supervisors. However, the last 2 programs were improvements of the 1st 2. Based on previous evaluations, certain topics had been incorporated in the succeeding training programs. For future training programs the following topics were suggested: Work Attitude, Force - field Analysis and Case Studies from local settings. It was the opinion of the 4 groups of respondents that the objectives of the course were fully met. In terms of content, the training had been rated Highly Satisfactory. The study conclude that the Supervisory Development Course offered at the National Center for Mental Health from 1980-1984, improved the competencies in terms of knowledge and behavior in on-the job performance of the participants and is therefore being recommended to be continued.